Piercing the doctrine of strict compliance in documentary credits: how strict is strict compliance? - Chirenje, Knowledge Mabharani (Department of Commercial Law, 2024)
Letters of credit have since time immemorial been the bedrock of international trade financing. Arguably, letters of credit have survived the test of time by the observance of the doctrine of strict compliance; that the documents presented by the vendor or provider of services must strictly comply with the terms and conditions of the credit. Lord Sumner put it thus, "It is both common ground and common sense that in such a transaction, the accepting bank can only claim indemnity if the conditions upon which it is authorised to accept are in the matter of the accompanying documents strictly observed. There is no room for documents which are almost the same, or which will do just as well. Business could not proceed securely on any other lines. The bank's branch abroad which knows nothing officially of the details of the transaction thus financed, cannot take upon itself to decide what will do well enough and what will not. If it does as it is told, it is safe; if it declines to do anything else, it is safe; if it departs from the conditions laid down, it acts at its own risk." The aim of this research is to investigate the extent of this strict compliance in letters of credit operation and the desirability or otherwise of relaxing the rigours of strict compliance. In doing so, it will put into context the general form and content of documentary credits, the current construction of the doctrine and critically investigate how strict is the strict compliance doctrine. Final thoughts will be given as to the possibilities of relaxation of the doctrine and a possible desirable interpretational position for Zimbabwe.